Sistem Informasi Inventory Barang Berbasis Web: Studi Kasus : Koperasi Kasongan Usaha Bersama Bantul - fatoni, fatoni fatoni; Sujarwadi, Agus (STMIK Palangkaraya, 2019)
Inventory system is a system that serves to know the inventory of goods in a place. Inventory systems are widely used or developed in a place with a variety of technologies. The existing problem at cooperative kasongan business together is not yet availability of inventory system of goods not efficient so that, when employees perform data collection sometimes still occur miscalculation because in data collection goods not yet computerized. Therefore, in this final project will be built web-based inventory information system,so that information about the stock of goods available in cooperative can be known clearly and in detail. This inventory application is built using the programming language Php and mysql as database and several other stages in the design of this system. The stages in the design of this system is the analysis and design of systems, system design, coding, system implementation and system testing. Based on the concept and design of this system then, it can be concluded that the web-based inventory of goods applications was built with the aim that in the management of data entry and discharge of goods more orderly and computerized so as to avoid the problem of miscalculation done by employees when collecting goods in cooperative Bantul.